2021
DOI: 10.1109/access.2021.3118554
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Diffusion of Medical Technologies Within Healthcare: A Systematic Review

Abstract: Implementing medical devices into a clinical setting is a complex and lengthy process. Existing models, such as Rogers' Diffusion of Innovation, try to elucidate this process, however, need to be updated to the evolving healthcare context as fewer than 7% of devices achieve implementation. The aim of this systematic review was to describe the barriers to diffusion in relation to this model to understand why so few technologies are implemented and how to address these challenges to mitigate risk during the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…Although medicine has advanced rapidly, and will continue to advance in the years to come, there are significant barriers that must be overcome to innovate and drive medicine forward. Each year the FDA receives around 22,000 applications for new products with only 7-9% eventually reaching the market [51]. However, according to the FDA, each year more novel products are approved with 132 being approved in 2020 alone indicating that innovation continues to grow [52,53].…”
Section: Framework and Barriers Of Innovation In Neurosurgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Although medicine has advanced rapidly, and will continue to advance in the years to come, there are significant barriers that must be overcome to innovate and drive medicine forward. Each year the FDA receives around 22,000 applications for new products with only 7-9% eventually reaching the market [51]. However, according to the FDA, each year more novel products are approved with 132 being approved in 2020 alone indicating that innovation continues to grow [52,53].…”
Section: Framework and Barriers Of Innovation In Neurosurgerymentioning
confidence: 99%
“…Despite this growth, various barriers have to be overcome to successfully innovate in medicine. One systematic review by Warty et al found that these barriers include regulation, technological challenges, lack of clinical evidence, health technology assessment, reimbursement, and adoption 51 . This supported what Bergsland et al found in 2014 [54].…”
Section: Framework and Barriers Of Innovation In Neurosurgerymentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the most common impacts on medical device innovation mentioned are regulatory processes, firm size, academia and industry, and pricing. One major deterrent to medical device innovation is the required regulatory processes [Warty et al, 2021;Bayon et al, 2016;Krucoff et al, 2012]. In addition to regulatory compliance decreasing the pace and increasing the cost of innovation, companies also point to the unpredictability of the regulatory process as a major deterrent.…”
Section: Background Innovation In Medicalmentioning
confidence: 99%
“…Comprehensive understanding of the impact of government policy on innovation is essential, yet most research in this area focuses on pharmaceuticals or biotechnology. For the research that does focus on medical devices in particular, regulation is commonly framed as one of the largest barriers to innovation [Bergsland et al, 2014;Warty et al, 2021]. Given this barrier, and evidence that there has been a decline in the rate of innovation at the industry level [Bayon et al, 2016], it is important to understand how both firms and government can encourage medical device innovation.…”
Section: Introductionmentioning
confidence: 99%